Prognostic factors in patients with advanced pancreatic cancer treated with gemcitabine alone or gemcitabine plus cisplatin: retrospective analysis of a multicenter study - Inal, A.; Kos, F. T.; Algin, E.; Yildiz, R.; Berk, V.; Unek, I. Tugba; Isikdogan, A. (Imprimatur Publications, 2012)
Purpose: The majority of patients with pancreatic cancer present with advanced disease. Systemic chemotherapy for patients with pancreatic cancer has limited impact on overall survival (OS). Patients eligible for chemotherapy should be selected carefully. The aim of this study was to analyse prognostic factors for OS in advanced pancreatic cancer patients treated with first-line palliative chemotherapy with gemcitabine alone or gemcitabine plus cisplatin. Methods: We retrospectively reviewed 343 locally advanced or metastatic pancreatic cancer patients who were treated with gemcitabine or gemcitabine plus cisplatin as first-line chemotherapy between December 2000 and June 2011. Fifteen potential prognostic variables were chosen for analysis. Univariate and multivariate analyses were conducted to identify prognostic factors associated with OS. Univariate and multivariate statistical methods were used to determine prognostic factors. Results: Among the 15 variables of univariate analysis, 6 were identified to have prognostic significance: stage (p<0.001), cholestasis (p=0.02), weight loss, prior pancreatectomy, serum CEA level (p<0.001) and serum CA19-9 level (p<0.001). In addition, age, chemotherapy and liver metastasis were of borderline significance (p=0.06). Multivariate analysis (Cox proportional hazard model) included the 6 significant prognostic factors of univariate analysis and showed that stage was independent prognostic factor for OS, as were weight loss, and serum CEA level. Conclusion: Stage, weight loss, and serum CEA level were identified as important prognostic factors for OS in advanced pancreatic cancer patients. These findings may also facilitate pretreatment prediction of OS and can be used for selecting patients for treatment.
Keywords: cancer; gemcitabine; pancreas; prognosis